Chromatin loops, gene positioning, and gene expression - Holwerda, Sjoerd; De Laat, Wouter (Frontiers in Genetics, 2012)
Technological developments and intense research over the last years have led to a better understanding of the three-dimensional structure of the genome and its influence on genome function inside the cell nucleus. We will summarize topological studies performed on four model gene loci: the α- and β-globin gene loci, the antigen receptor loci, the imprinted H19-Igf2 locus and the Hox gene clusters. Collectively, these studies show that regulatory DNA sequences physically contact genes to control their transcription. Proteins set up the three-dimensional configuration of the genome and we will discuss the roles of the key structural organizers CTCF and cohesin, the nuclear lamina and the transcription machinery. Finally, genes adopt non-random positions in the nuclear interior. We will review studies on gene positioning and propose that cell-specific genome conformations can juxtapose a regulatory sequence on one chromosome to a responsive gene on another chromosome to cause altered gene expression in subpopulations of cells.